Association between ultrasound-quantified cardiac mechanical dyssynchrony and left heart function and remodeling - Su, Xiaoling; Guan, Lina; Wu, Zhisheng; Yang, Lingjie; Mu, Yuming (Quantitative imaging in medicine and surgery, 2025)
Ultrasound can be used to quantitatively assess cardiac mechanical dyssynchrony. The differences between and prognoses of chronic heart failure (CHF) patients with left heart dysfunction and remodeling for different combinations of intra-left ventricular (intra-LV) and interventricular (inter-V) mechanical dyssynchrony or synchrony remain unclear. This study sought to assess the relationships among intra-LV dyssynchrony, inter-V dyssynchrony, and left heart function and remodeling in CHF patients. CHF patients with a left ventricular (LV) ejection fraction <50% and control subjects presenting with no abnormalities in their medical history or on physical examination, electrocardiography, or echocardiography during the concurrent physical assessment were retrospectively included in the study. The patients were divided into four groups based on the standard deviation of the time to peak longitudinal strain in 12 LV segments according to speckle-tracking echocardiography (SD ) and the interventricular mechanical delay (IVMD). All the patients underwent speckle-tracking echocardiography (STE) to assess LV and left atrial (LA) function, and the QRS width and echocardiographic findings were recorded. All patients were followed up for any cardiac events from the date of enrollment. A multivariable analysis was performed, and the Kaplan-Meier method was used to assess cardiac events. In total, 52 control subjects (60.79±13.3 years, 32 males) and 208 patients (59.9±12.6 years, 160 males) were included in the study. Of the subjects, 58 had intra-LV and interventricular synchrony (Intra Inter ), 40 had intra-LV synchrony and interventricular dyssynchrony (Intra Inter ), 51 had intra-LV dyssynchrony and interventricular synchrony (Intra Inter ), and 59 had intra-LV and interventricular dyssynchrony (Intra Inter ). There was no significant difference in the LV and LA function between the Intra Inter and Intra Inter groups (P>0.05), or between the Intra Inter and Intra Inter groups (P>0.05). The Intra Inter and Intra Inter groups had lower LV and LA function than the Intra Inter and Intra Inter groups (P<0.05). The SD was more strongly associated with LV functional deterioration and LV remodeling than IVMD (P 0.05). The multivariable linear regression analysis indicated that SD independently predicted global longitudinal strain (GLS) (R =0.834, P<0.001). LA functional deterioration was closely related to LV functional impairment. Compared with the other CHF groups, the Intra Inter group had a wider QRS complex, a greater LV end-diastolic volume index, and a greater incidence of cardiac events, and a greater proportion of patients in the Intra Inter group received cardiac resynchronization therapy (CRT) (P 0.05). Compared with IVMD, intra-LV dyssynchrony is more strongly associated with LV dysfunction and remodeling in CHF patients, and LA dysfunction is predominantly contingent upon/is largely dependent on LV dysfunction. When both intra-LV and inter-V dyssynchrony are present, the extent of the LV volumetric increase and electrical remodeling is the most pronounced. This patient group had a higher incidence of cardiac events during follow up and a greater likelihood of receiving CRT.